2020
DOI: 10.4068/cmj.2020.56.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Coronary Artery Calcification on Intradialytic Blood Pressure Patterns in Patients Receiving Maintenance Hemodialysis

Abstract: Intradialytic blood pressure abnormalities are associated with adverse outcomes in patients with end-stage renal disease on dialysis. Vascular calcification is a common complicating feature, but whether this complication results in intradialytic blood pressure abnormalities remains uncertain. Therefore, this study investigated the relationship between coronary artery calcium score and intradialytic blood pressure abnormalities in patients with end-stage renal disease on maintenance hemodialysis. Thirty-six pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
0
5
3
Order By: Relevance
“…16 The abdominal aortic calcification score is the most reliable predictor of coronary artery calcification in patients undergoing dialysis, 17 and aortic arch calcification is strongly associated with coronary artery calcification. 18 The discrepancy between Yeo et al's findings 9 and our findings in terms of the relationship between CACS and IDH may be due to the method used to quantify the CACS. We quantified the CACS using ECGgated CT, whereas Yeo et al used non-ECG-gated CT. 9 We consider some possible explanations for the observed relationship between CACS and IDH.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…16 The abdominal aortic calcification score is the most reliable predictor of coronary artery calcification in patients undergoing dialysis, 17 and aortic arch calcification is strongly associated with coronary artery calcification. 18 The discrepancy between Yeo et al's findings 9 and our findings in terms of the relationship between CACS and IDH may be due to the method used to quantify the CACS. We quantified the CACS using ECGgated CT, whereas Yeo et al used non-ECG-gated CT. 9 We consider some possible explanations for the observed relationship between CACS and IDH.…”
Section: Discussioncontrasting
confidence: 99%
“…IDH is associated with abdominal aortic calcification 7 and aortic arch calcification 8 in patients undergoing HD. However, Yeo et al reported that the CACS was not correlated with the decrease in intradialytic SBP and nadir SBP in 36 patients undergoing HD 9 . The CACS in the chronic kidney disease (CKD) population may be less specific for the atherosclerotic burden and is a composite of medial and intimal calcification of the coronary arteries 14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High BP causes cardiovascular injury. High BP is associated with coronary artery disease ( Yeo et al, 2020 ), cardiac systolic dysfunction, and left ventricular hypertrophy ( Chao et al, 2015 ). There are cause-and-effect relationships between these factors and IDH.…”
Section: Discussionmentioning
confidence: 99%